CYCLOSPORINE INDUCED GINGIVAL HYPERPLASIA IN KIDNEY TRANSPLANT: A CASE REPORT AND REVIEW OF THE LITERATURE - Gaphor, Shanaz Mohammad; Abdulkareem, Saeed Abdullatteef; Abdullah, Mustafa Jamel (European Scientific Journal, ESJ, 2014)
Kidney transplantation is considered the best therapeutic option for end stage renal disease (ESRD). Cyclosporine is a potent immunosuppressive drug used to prevent graft rejection. Gingival hyperplasia is one of the collateral effect of cyclosporine, the exact pathogenesis of cyclosporine induced gingival hyperplasia is uncertain, and it may interfere with normal oral functions causing unpleasant appearance, carry psychological impacts and leads to difficulty in maintaining good oral hygiene. A 28 year old male patient reported to the department of Oral Medicine of the School of dentistry, University of Sulaimani, he had renal transplantation and he is on long term immunosppressive drug (cyclosporine), the patient complains of gingival swelling, intraoral examination revealed severe generalized gingival hyperplasia, periodic oral examination of kidney transplant patients who are on long term cyclosporine drug treatment is important to monitor any signs of gingival hyperplasia, reassurance and management based on general medical condition of the patient.